The gastrointestinal system in the critically ill cirrhotic patient - Olson, Jody C (Current opinion in critical care, 2020)
ICU admissions due to complications of advanced liver disease continue to rise. Among indications for admission to the ICU in patients with cirrhosis, gastrointestinal issues such as bleeding are common. In patients in whom gastrointestinal issues are not the principal indication for ICU, gastrointestinal issues such as nutrition and ileus remain important concerns for generalized intensive care support. This review highlights current trends in management of gastrointestinal issues in patients with cirrhosis admitted to the ICU. General management of upper gastrointestinal bleeding remains largely unchanged. Improvements in interventional techniques have increased the options for difficult to control bleeding, these include the development of expandable esophageal stents and expanded experience with advanced interventional radiology techniques for the management of bleeding gastric varices. Frailty as an important prognostic marker in advanced liver disease and liver transplantation is the subject of several new studies and serves to highlight the importance of nutrition in the management of the critically ill cirrhotic patient. Gastrointestinal complications are frequent in the critically ill cirrhotic patient. Recognition and intervention in a timely manner may minimize morbidity and mortality and result in improved outcomes for this vulnerable population.